Osseointegrated Transcutaneous Device for Amputees: A Pilot Large Animal Model - Brian T. Grisez; Andrew E. Hanselman; Karim W. Boukhemis; Trapper A. J. Lalli; Brock A. Lindsey (Advances in Orthopedics)
Traditional above-the-knee amputation prosthetics utilize a stump-socket interface that is well-known for skin/socket problems, sitting difficulty, disuse osteopenia, and increased work of ambulation. As a result, we evaluated a novel osseointegrated transcutaneous implant in a large animal. The implant was designed to promote osseointegration at the bone-implant interface and minimize complications. As proof of concept, four Dorset sheep underwent a two-stage surgery for forelimb placement of an osseointegrated transcutaneous implant utilizing Compress® technology (Biomet, Inc., Warsaw, IN). Two sheep received a long anchor plug (90 mm long x 9 mm in diameter) and two received a short anchor plug (46 mm long x 9 mm in diameter). Sixteen weeks after the initial surgery, the operative limbs, along with the attached implant, underwent radiographic and histological analysis for osseointegration. Periprosthetic fractures occurred in the two animals that received the longer internal prosthesis; one healed with splinting and the other animal underwent a second surgical procedure to advance the amputation site more proximal. No fractures occurred in the shorter internal prosthesis group. There was no histological evidence of infection and none of the transcutaneous adapters failed. Bone-implant osseointegration was demonstrated in two of three limbs that underwent histological analysis. This unique implant demonstrated osseointegration without transcutaneous adapter failure, all while displaying minimal infection risk from the outside environment. Although it involved short-term follow-up in a limited number of animals, this pilot study provides a platform for further investigation into the valid concept of using Compress® technology as an endo-exo device.